2019
DOI: 10.1108/ijif-01-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity creation and bank performance: evidence from MENA

Abstract: Purpose Islamic banks have significantly different balance sheets from their conventional counterparts, leading to different implications in relation to liquidity creation compared to conventional banks. This work, first, investigates the liquidity creation of conventional and Islamic banks in Middle Eastern and North African (MENA) countries between 2011 and 2016. It then tests the relationship between liquidity creation and performance of these banks. Design/methodology/approach It uses the data of 491 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 36 publications
10
41
1
3
Order By: Relevance
“…Despite having low net worth/assets ratios, Banks 12 and 14 generate more liquidity per asset compared to conventional banks and operate more effectively. This finding is in line with the literature, which has found that Islamic banks create more liquidity per asset compared to conventional ones (Berger & Bouwman, 2009;Berger, Allen, Boubakri, Guedhami, & Li, 2019;Sahyouni & Wang, 2019). Banks 12 and 14 also have the largest total assets among the Islamic banks, supporting the view that the stabilising role of Islamic banks strengthens when they become larger (Ibrahim & Rizvi, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Despite having low net worth/assets ratios, Banks 12 and 14 generate more liquidity per asset compared to conventional banks and operate more effectively. This finding is in line with the literature, which has found that Islamic banks create more liquidity per asset compared to conventional ones (Berger & Bouwman, 2009;Berger, Allen, Boubakri, Guedhami, & Li, 2019;Sahyouni & Wang, 2019). Banks 12 and 14 also have the largest total assets among the Islamic banks, supporting the view that the stabilising role of Islamic banks strengthens when they become larger (Ibrahim & Rizvi, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…where NPF has no effect on profitability [17]. The results of this study are in line with the findings of previous studies, where liquidity does not affect profitability [3], [18], [16], [19]. Bank liquidity does not affect profitability.…”
Section: Resultssupporting
confidence: 91%
“…Risk identification is the process of initiating actions; creating awareness, common sense, and commitment; and clarification of expectations. Board risk management committee if not carried out correctly will lead to future defaults (Sahyouni and Wang 2019).…”
Section: Literature Reviewmentioning
confidence: 99%